UPAYA MENINGKATKAN DISIPLIN GURU BAHASA INDONESIA DALAM MENGAJAR MELALUI PEMBINAAN DI SDN 001 ROKAN IV KOTO - Pauzar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on observations of SDN 001 Rokan IV Koto, discovered the phenomenon among others, there are many teachers who come late to school, there is still a lack of discipline in the Indonesian teachers teaching in the classroom, the teacher is often late to class. The purpose of this research is to investigate the Indonesian teacher discipline in teaching can be improved through coaching in SDN 001 Rokan IV Koto. Subjects in this study were teachers SDN 001 Rokan IV Koto Indonesian in as many as 13 teachers. From the description of data processing and discussion it was concluded that the discipline of Indonesian teachers in teaching obtained in the first cycle of 56% with a good category and the second cycle increased to 74% in both categories. This means that development activities can improve the discipline of Indonesian teachers in teaching in SDN 001 Rokan IV Koto is successful.